2012
DOI: 10.1002/ajh.23163
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life in nonsplenectomized immune thrombocytopenia patients receiving romiplostim or medical standard of care

Abstract: Immune thrombocytopenia (ITP) is an autoimmune disorder characterized by platelet destruction and insufficient platelet production. The resulting thrombocytopenia reduces patient health-related quality of life (HRQOL). In a randomized, open-label, 52-week study of nonsplenectomized ITP patients treated with romiplostim or medical standard of care (SOC), patients completed the 10-scale ITP-patient assessment questionnaire (PAQ) at the start of the study and after 12, 24, 36, 48, and 52 weeks of treatment. HRQOL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 19 publications
2
72
0
3
Order By: Relevance
“…The overall results were better, with fewer experiencing treatment failure or proceeding to splenectomy with associated clinically important improvements in their ITP-PAQ scores. Statistically significant improvements in symptoms, bother, activity, psychological health, fear, social activity and overall HR-QOL were seen (p < 0.05) [Kuter et al 2010a[Kuter et al , 2012b, confirming the impact on quality of life in patients with thrombocytopenia and the importance to the patient in its reversal.…”
Section: Quality-of-life Analysesmentioning
confidence: 70%
“…The overall results were better, with fewer experiencing treatment failure or proceeding to splenectomy with associated clinically important improvements in their ITP-PAQ scores. Statistically significant improvements in symptoms, bother, activity, psychological health, fear, social activity and overall HR-QOL were seen (p < 0.05) [Kuter et al 2010a[Kuter et al , 2012b, confirming the impact on quality of life in patients with thrombocytopenia and the importance to the patient in its reversal.…”
Section: Quality-of-life Analysesmentioning
confidence: 70%
“…After dexamethasone treatment, 5 patients responded and 5 achieved CR. All patients achieved either R or CR by the time treatment with eltrombopag was complete (median 5 days, range [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. The CR rate was 83.3%, whereas the R rate was 16.7%.…”
Section: Resultsmentioning
confidence: 99%
“…4 Corticosteroids remain the standard of care, but high failure/relapse rates and considerable adverse effects from long-term use continue to stimulate the search for better treatments. 3,5,6 We and others have reported sustained response rates ranging from 58% to 76% using rituximab plus dexamethasone as a frontline therapy. [7][8][9][10] Eltrombopag is a thrombopoietin (TPO) nonpeptide mimetic that has been shown to raise the Plt in both continued long-term administration and in a repeated short-term administration in chronic ITP.…”
Section: Introductionmentioning
confidence: 99%
“…32,33 The significantly shortened TTR in the combination group was likely to be attributed to the fast onset of rhTPO. 20,34 This result suggested that rhTPO could be used as a salvage treatment and combined with RTX in the treatment of ITP.…”
Section: Discussionmentioning
confidence: 99%